2015
DOI: 10.1002/etc.2928
|View full text |Cite
|
Sign up to set email alerts
|

On‐site, serial exposure of female fathead minnows to the Elkhorn River, Nebraska, USA, spring agrichemical pulse

Abstract: In the Midwestern United States, waterways such as the Elkhorn River experience an annual spring pulse of runoff that carries sediments, nutrients, and organic compounds downstream. The objective of the present study was to elucidate relationships between contaminant load in Elkhorn River water and biological impacts on female fathead minnows throughout the entire spring agrichemical pulse. Fish were maintained in on-site outdoor microcosms at the Elkhorn River Research Station. The start of the spring pulse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Briefly, beginning April 15, 2015 atrazine test strips were used to test whether concentrations of atrazine in surface water in the Elkhorn River were above or below 3 μg·L . These test strips have been demonstrated to accurately detect the presence of atrazine and other triazine herbicides at 3 μg·L −1 in surface water (US EPA 2004), with further confirmation of there accuracy by previously collected field data (Knight et al 2013;Ali and Kolok 2015). Tests were conducted every three to four days where the detection of three consecutive positive atrazine strips determined the start of the spring agrichemical pulse on May 8, 2015 (Fig.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 56%
See 4 more Smart Citations
“…Briefly, beginning April 15, 2015 atrazine test strips were used to test whether concentrations of atrazine in surface water in the Elkhorn River were above or below 3 μg·L . These test strips have been demonstrated to accurately detect the presence of atrazine and other triazine herbicides at 3 μg·L −1 in surface water (US EPA 2004), with further confirmation of there accuracy by previously collected field data (Knight et al 2013;Ali and Kolok 2015). Tests were conducted every three to four days where the detection of three consecutive positive atrazine strips determined the start of the spring agrichemical pulse on May 8, 2015 (Fig.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 56%
“…Exposure of all fathead minnow larvae was conducted at the Elkhorn River Research Station (ERRS) where previous field studies have identified biological impacts and changes in endocrine responsive gene expression following in situ exposure to agricultural runoff (Knight et al 2013;Ali and Kolok 2015;Zhang et al 2015;Ali et al 2016). The ERRS is an open-air facility located approximately 10 km upstream from the confluence of the Elkhorn and Platte Rivers, Nebraska, USA.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 99%
See 3 more Smart Citations